PENINGKATAN KUALITAS TENAGA KEPERAWATAN DALAM DETEKSI DINI KELAINAN KAKI DIABETES BERBASIS APLIKASI DENGAN METODE MCP - Heri Kristianto* (Universitas Muhammadiyah Jember, 2016)
This study was aimed to provide training for nurses in the detection of diabetic foot disorders. The training method used were MCP (Mentoring, Clinical Supervision, Preceptoring). The target of the study were nurses who are working at Sumber Sentosa Hospital (RSSS) and Madiun Regional Public Hospital. Cognitive evaluation from the participants in Sumber Sentosa Hospital (RSSS) showed an increase of 27.65%, while in the Madiun Regional Public Hospital showed an increase of 23%. Psychomotor evaluation at both hospitals showed that 90% of nurses can implement the appropriate procedures based on the examination manual. Judging from the level of participation during the study, data showed that 100% of nurses in the Madiun Regional Public Hospital attended and followed the activities of two-days training, while at the RSSS showed 96% of nurses followed the activities. The satisfaction level of participants on the training materials showed by value of 18.6 (measuring scale of 6-24). The satisfaction level of participants on the operational training showed by value of 20,58 (measuring scale of 7-28). The satisfaction level of participants on the instructors showed by value of 26.13 and 25.35 (measuring scale of 8-32). Keywords: Nursing, Diabetic Foots, MCP, Application